2014
DOI: 10.1039/c4em00448e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the photolysis of pharmaceuticals within a river by 2 year field observations and toxicity changes by sunlight

Abstract: To improve the risk assessment of pharmaceuticals, it is helpful to know how rapidly they are removed from river water. Direct photolysis by sunlight could be an important process, but so far few studies have attempted to compare modeled with actual losses in a river. Therefore, we quantified natural attenuation by monitoring 56 pharmaceuticals and personal care products over 2 full years in a 2.6 km stretch of an urban river. In addition, to screen photoproducts, we used the Microtox test with Vibrio fischeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The toxicity unit (TU = 100/EC 50% , EC 50% is the effect concentration at which 50% of effect occurs; the higher the TU, the higher the toxicity) and G L level (dilution level at which the inhibition is below 20% for the first time; the higher the G L level, the higher the toxicity) at 90 min of UVA irradiation doubles compared to an untreated diclofenac solution. The evaluation of the toxicity of diclofenac treated with UVA light is controversial discussed [ 52 , 56 , 57 , 58 ]. But the conditions (concentration of diclofenac, UVA light wavelength, UVA light intensities, additives in water, tested biological organism) do differ and lead to different transformation products and concentrations of these products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicity unit (TU = 100/EC 50% , EC 50% is the effect concentration at which 50% of effect occurs; the higher the TU, the higher the toxicity) and G L level (dilution level at which the inhibition is below 20% for the first time; the higher the G L level, the higher the toxicity) at 90 min of UVA irradiation doubles compared to an untreated diclofenac solution. The evaluation of the toxicity of diclofenac treated with UVA light is controversial discussed [ 52 , 56 , 57 , 58 ]. But the conditions (concentration of diclofenac, UVA light wavelength, UVA light intensities, additives in water, tested biological organism) do differ and lead to different transformation products and concentrations of these products.…”
Section: Resultsmentioning
confidence: 99%
“…But the conditions (concentration of diclofenac, UVA light wavelength, UVA light intensities, additives in water, tested biological organism) do differ and lead to different transformation products and concentrations of these products. Hanamoto et al [ 57 ] and Kovacic et al [ 52 ] identify a decrease of toxicity towards Vibrio fischeri after sunlight and UVA (365 nm) light treatment, respectively. Contrary, Schmitt-Jansen [ 58 ] studies showed an increase of toxicity towards the algal S. vacuolatus after day light treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Many PPCPs have been found to be photodegradable under sunlight irradiation (Hanamoto et al 2014;Lam et al 2004;Lin et al 2006;Matamoros et al 2008). Photodegradation of PPCPs involves both direct photolysis and indirect photolysis.…”
Section: Photodegradationmentioning
confidence: 99%
“…The toxicity of compounds derived from the incomplete degradation of pharmaceuticals often is greater than that of the original pharmaceutical. Photodegradation is one of the most important factors to consider in the environmental ecotoxicology of pharmaceuticals in the aquatic environment . Furthermore, some pharmaceuticals, upon photoexcitation, become phototoxins with the potential to modify biological systems.…”
Section: Introductionmentioning
confidence: 99%